Paper plate machine - Suhaimi, Muhamad Hafiz; Hassan, Mohd Fahrul; Amirudin, Mohamed Syafiz; Mohamad, Siti Shafika; Ahmad Shah, Mohamaed Hakim; Ngah, Muhammad (Penerbit UTHM, 2017)
In recent years natural fibers appear to be the outstanding materials which come as the viable and abundant substitute for the expensive and nonrenewable synthetic fiber. Natural fibers like sugar cane, banana, , oil palm, kenaf and coir has been used as reinforcement in thermoplastic composite for applications in consumer goods, furniture, low cost housing and civil structures. Pineapple leaf fiber (PALF) is one of them that have also good potential as reinforcement in thermoplastic composite. It is the objective of the current research to characterize PALF and to investigate the effect of fiber treatment on the mechanical properties of PALF reinforced polypropylene (PP) composite. Figure 6.1 show the example of pineapple used.